Features of fungal colonization of newborns from mothers with vulvovaginitis - A. S. Eiberman; Y. V. Chernenkov; L. G. Bochkova (LLC "Diagnostics and Vaccines", 2020)
The aim of this study was to determine the frequency and etiological structure of fungal colonization of newborns from mothers with vaginal infections taking into account the methods of delivery, gestational age and body weight of the child. Material and methods. 80 women clinically suspicious of fungal vulvovaginitis were examined at 16-22 weeks of gestation. Samples from the loci of probable fungal colonization in their children (81 newborns, one twins) were collected on 2-3 and 10-5 days of life. Samples were plated on Sabouraud agar and Czapek agar, followed by species identification by API Candida - api 20 C AUX yeast assay. Results. Positive results were found in 23 (28.8%) mothers (Candida spp.) And 44 (54.3%) newborns (Candida spp., Aspergillus flavus, Penicillium expansum Link, Mucor racemosus). Isolates of 7.4% of full-term infants were completely identical to the maternal microflora (Candida spp.). The remaining 19 (23.5%) premature infants were found to have molds of fungi, which indicates the nosocomial nature of the infection. A statistically significant relationship between the type of delivery and fungal colonization in newborns was found in the early neonatal period (2-3 days of life).